Evaluation of platelet activity by multiple electrode impedance aggregometry in acute coronary syndromes: pilot study in a Brazilian tertiary-care public hospital - De Lorenzo,A. (2019)
There is no definite recommendation for testing platelet aggregation (PA) in acute coronary syndromes (ACS) due to inconclusive evidence on the usefulness of platelet function tests to guide therapy and improve clinical outcomes. The evaluation of PA with multiple electrode impedance platelet aggregometry (MEA) may be useful to manage antiplatelet therapy and possibly influence patient outcome. The primary aim of this study was to measure PA with MEA in Brazilian patients with ACS and evaluate the association between PA and adverse clinical outcomes. Forty-seven consecutive patients admitted with ACS to a Brazilian tertiary-care public hospital were studied and PA was evaluated using MEA. Patients were followed for six months for the occurrence of all-cause death, acute myocardial infarction, or stroke. Suboptimal inhibition of PA was found in 7 patients (14.9%); 5 (10.6%) in response to ASA (acetylsalicylic acid), 2 (5.0%) to clopidogrel, and none to ticagrelor. Inadequate PA inhibition in response to ASA was significantly associated with the composite end point, but there was no significant association for insufficient PA inhibition in response to clopidogrel. This study suggested that the evaluation of PA in ACS using MEA may identify non-responders to ASA. Larger studies are necessary to define, in a public health scenario, the value of MEA in the management of ACS.